Pengaruh Lingkungan Sosial terhadap Sikap Konservasi Siswa di Medan - Lestari, Wiwik; Azhari, Ichwan (IAIN Madura, 2024)
This study aims to explore the influence of the social environment on the attitude of primary school students in Medan City towards coastal conservation. Through a qualitative approach, this research identifies how interactions with family, friends, and community can shape students' views on the importance of coastal conservation. The results showed that a positive social environment can increase students' awareness and participation in conservation activities, while a less supportive environment can inhibit pro-environmental attitudes. The findings are expected to provide insights into developing more effective environmental education programs in primary schools.. Keywords: Social environment, students' attitudes, coastal conservation, environmental education.